On the origin of the late-flowering ppd-H1 allele in barley - Rajiv Sharma; Salar Shaaf; Kerstin Neumann; Peter Civan; Yu Guo; Martin Mascher; Michal David; Adnan Al-Yassin; Hakan Özkan; Tom Blake; Sariel Hübner; Nora P. Castañeda-Álvarez; et al. (Theoretical and Applied Genetics, 2025)
To breed for climate resilient crops, an understanding of the genetic and environmental factors influencing adaptation is critical. Barley provides a model species to study adaptation to climate change. Here we present a detailed analysis of genetic variation at a major photoperiod response locus and relate this to the domestication history and dispersal of barley. The PPD-H1 locus (a PSEUDO-RESPONSE REGULATOR 7 ) promotes flowering under long-day conditions, and a natural mutation at this locus resulted in a recessive, late-flowering ppd-H1 allele. This mutation proved beneficial in high-latitude environments such as Northern Europe, where it allows extended vegetative growth during long spring days. We infer the origin of the mutated late-flowering ppd-H1 allele by re-sequencing a large geo-referenced collection of 942 Hordeum spontaneum , 5 Hordeum agriocrithon and 1110 domesticated ( Hordeum vulgare ) barleys. We demonstrate that the late-flowering phenotype originated from Desert-type wild barley in the Southern Levant and present evidence suggesting a post-domestication origin of the mutated ppd-H1 allele.